Taxation mechanism and instruments of state antycrisis policy: conceptional approach to use - Olena Filatova (Cхід, 2013)
The object of research in article is conceptional approach to forming of mechanism of State untycrisis policy. Argu, that in modern Ukraine it mast be base at taxation mechanism and instruments of safeguarding antycrisis State economic development.